Long non-codingRNA (lncRNA) TUG1 and the prognosis of cancer: a meta-analysis - Yu, X-H.; Guo, W.; Zhang, J.; Ma, C.; Chu, A-J.; Wen, B-L.; Zhang, X.; Yan, X-Y.; Wu, C-M.; Wang, D-M.; Qu, Y-L. (Cellular and Molecular Biology, 2017)
Some studies assessed the association between lncRNA taurine-upregulated gene 1 (TUG1) and the survival in cancer. However, the results were inconclusive. Therefore, we performed a meta-analysis to determine this association. We used the following electronic databases to search for eligible literature: PubMed, Embase, Chinese National Knowledge Infrastructure (CNKI) and Wanfang. We used ORs and 95% CIs to measure the association between TUG1 and the survival of cancer. There was no significant association between TUG1 and OS of cancer (HR=1.26, 95% CI=0.97-1.64). In the subgroup analysis by cancer type, significant association could be find in osteosarcoma (HR=1.72, 95% CI=1.27-2.32) and digestive system's tumors (HR=1.66, 95% CI=1.04-2.66). In conclusion, this meta-analysis study indicated that TUG1 might associate with the OS of osteosarcoma and digestive system's tumors.